Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1103/physrevlett.98.058304
|View full text |Cite
|
Sign up to set email alerts
|

Forces of Interaction between DNA-Grafted Colloids: An Optical Tweezer Measurement

Abstract: Optical tweezers are employed to measure the forces of interaction between single DNA-grafted colloids. Parameters to be varied are the length of the DNA, the grafting density, and the ion concentration of the surrounding medium. From the measured force-separation dependence an interaction length at a given force is deduced. It shows in the mushroom regime a scaling with the grafting density which levels off for brushes. For the latter the transition from an osmotic to a salted brush can be traced in detail by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 40 publications
2
86
0
1
Order By: Relevance
“…Strong polyelectrolyte brushes that have so far been reported in the literature were predominantly made of a few different molecules: poly(styrene sulfonate) (PSS), 20,50−53 poly(vinyl methyl pyridinium) (PVP), 54 and double-stranded DNA. 55,56 When compared to these brushes, HA brushes reveal particular features.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Strong polyelectrolyte brushes that have so far been reported in the literature were predominantly made of a few different molecules: poly(styrene sulfonate) (PSS), 20,50−53 poly(vinyl methyl pyridinium) (PVP), 54 and double-stranded DNA. 55,56 When compared to these brushes, HA brushes reveal particular features.…”
Section: ■ Discussionmentioning
confidence: 99%
“…On the other hand, systems with non-trivial interactions can be constructed. This includes charged particles which interact over a range of a few diameters [22], polymer coated particles interacting via mushroom-like potentials [23] or polymer coils, which in a good solvent behave effectively like soft, Gaussian-profiled particles [24]. The systematic molecular dynamics simulations for various combinations of repulsions and attractions in the systems have also shown that unexpected effects can be encountered, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The force F (D) and the surface-to-surface separation D between two identical, negatively charged DNA-grafted colloids is measured using optical tweezers in a identical set-up as used in Ref. [13].We employed colloidal particles with a hard core radius R c = 1100 nm, on which DNA-strands with various numbers of base pairs (bp) and grafting densities σ were chemically anchored. The brush has only a slight deviation from planarity, which allows us to relate also to known facts from planar PE-brushes in what follows.…”
mentioning
confidence: 99%